ANALYSIS OF HIGH SCHOOL STUDENTS' CRITICAL THINKING SKILLS IN TRIGONOMETRY MATERIAL VIEWED FROM A MATHEMATICAL GROWTH MINDSET - Choirunisa Choirunisa; Nailis Safiro; Mentari Mentari; Yusuf Hartono; Darmawijoyo Darmawijoyo (Universitas Jenderal Soedirman, 2026)
This study aims to describe students' critical thinking skills in solving trigonometry problems in terms of their Mathematical Growth Mindset level. This study uses a descriptive qualitative approach with high school students from a school in Palembang as subjects. These students are classified into high, medium, and low growth mindset categories. Data were collected through questionnaires, context-based critical thinking tests on trigonometry, and in-depth interviews. Data analysis was conducted based on critical thinking ability indicators, namely interpretation, analysis, evaluation, and inference. The results showed that students with a high mathematical growth mindset were able to consistently meet all critical thinking indicators. Students with a moderate growth mindset were able to meet the indicators of interpretation, analysis, and inference, but were not yet optimal in the evaluation indicator because they still relied on intuitive reasoning and did not perform explicit mathematical checks. Meanwhile, students with a low growth mindset showed limitations in almost all critical thinking indicators. These findings indicate that Mathematical Growth Mindset plays an important role in the quality of students' critical thinking in trigonometry. Therefore, mathematics learning needs to be designed to foster a growth mindset in order to continuously improve students' critical thinking skills.